MODELING TO IMPROVE THE PERFORMANCE OF REVERSE POWER RELAY IN GENERATOR - Zakri, Azriyenni Azhari; Rozi, Fahrul (SINERGI, 2020)
The generator is the primary component in electricity generation and requires a protection system from internal and external interference that occurs. This study considers how to improve the performance of relays in power plants. A model of a generator that is executed in a fault condition to reset the protective equipment, namely Reverse Power Relay (RPR). The study is intended to model the state of internal and external fault on the generator by applying a working principle of RPR. The model is designed to anticipate the actual fault in the generator. The simulation results obtained output such as; active power, current and time delay relay. The RPR reset of the generator system is applied to the generator in Riau Power. The RPR is installed on the generator is -612 kW, equivalent to 30%, the relay delay time is 0.2 seconds. Based on standardization, the return of power reaches a maximum of -12.66 MW, which is captured 50% with a maximum replacement of 30 seconds. Results of the RPR simulation have been validated with the IEEE standard at a time delay that corresponds to the percentage of reverse power settings installed at 6% and a time delay of 0.6%. Finally, to maximize the protection system on the generator, adjust 50% to 95% of the installed settings. It can be said that the system is able to increase generator protection and minimize the impact of internal or external fault.